Reclaiming The Faravahar : Zoroastrian Survival in Contemporary Tehran - Fozi, Navid (Book collections on Project MUSE., 2014)
This book is the first ethnographic study of contemporary Zoroastrians in Tehran. Examining hundreds of ritual performances, Navid Fozi shows how Zoroastrians define their identity and values in an area long marked by conflict between the Shi'a and Sunnis. He focuses on two main concerns for Zoroastrians: continuity with the past as evidenced by their claim to be the most authentic Iranians, as well as their attempts to stand apart from the dominant Shi'a. Fozi also provides a look at the challenges Zoroastrians have faced over the centuries while exploring how today's members are working to remain relevant in a tumultuous regional and global context.